2019
DOI: 10.1177/1741659019881040
|View full text |Cite
|
Sign up to set email alerts
|

The reification of structural violence in video games

Abstract: The Grand Theft Auto franchise features prominently within existing research exploring graphic, virtual, lawless, and damagingly realistic interpersonal violence within video games. Following a review of this literature, we empirically interrogate notions of the ‘realistic’ and the ‘violent’ during gameplay, finding that the undertones of systemic, structural, capitalistic violence are experienced by players as providing the gritty sense of the ‘real’ that the game has been criticised for. Using Galtung’s conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…This is one area where we want to push back, a little, against the criticisms of our work in this collection. It is certainly true that questions of sexism and racism in gaming have received analysis well beyond what Games of Empire provided (Bulut, 2020;Denham, Hirschler, & Spokes, 2019;Kishona & Leonard, 2018;Malkowski & Russworm, 2015;Patterson, 2020;Phillips, 2020;Shaw, 2015), and this vital work is continued in the essays in this issue by Cody Mejeur et al and Ergin Bulut. However, the racialization and gendering of games culture were not neglected in Games of Empire.…”
Section: Video Gaming's Violent Intersectionsmentioning
confidence: 99%
“…This is one area where we want to push back, a little, against the criticisms of our work in this collection. It is certainly true that questions of sexism and racism in gaming have received analysis well beyond what Games of Empire provided (Bulut, 2020;Denham, Hirschler, & Spokes, 2019;Kishona & Leonard, 2018;Malkowski & Russworm, 2015;Patterson, 2020;Phillips, 2020;Shaw, 2015), and this vital work is continued in the essays in this issue by Cody Mejeur et al and Ergin Bulut. However, the racialization and gendering of games culture were not neglected in Games of Empire.…”
Section: Video Gaming's Violent Intersectionsmentioning
confidence: 99%
“…Esse avanc ¸o permitiu que jogos pudessem usar elementos cinematográficos, como atuac ¸ão, cinematografia e dublagens oriundas de filmes, para dar um senso de escala, personalidade e realismo [Burelli 2016]. Em contra partida, trouxe uma preocupac ¸ão social sobre a violência que jogadores, muitos deles, adolescentes e crianc ¸as, estavam expostos, mesmo que de forma virtual [Denham et al 2021]. A preocupac ¸ão de pais e responsáveis sobre o conteúdo dos jogos, levou à criac ¸ão de órgãos dedicados a classificac ¸ão etária de jogos [Historian 2016].…”
Section: Elementos Empáticos Na 5ª Gerac ¸ãO (1993 -2006)unclassified
“…Even more significant is the possibility of a reciprocal reinforcement between structural violence incorporated into video games and the real-world environment that is reflected, possibly contributing to broader discourses of militarisation (Schulzke, 2013). Denham et al (2021) found that 'structural forms of violence [in video games] are seductive in their ability to contribute to the players' sense of being 'actually there' (p. 98). In fact, structural violence appears to have a stronger effect on game immersion than graphic first-person (direct) violence.…”
Section: Tech-facilitated Structural Violencementioning
confidence: 99%